Efektivitas Kinerja Pegawai UPTD Pasar Betung Kabupaten Banyuasin - Asteriniah, Femi (Jurnal Publisitas, 2020)
This research is entitled Effectiveness of Employee Performance at UPTD Pasar Betung, Banyuasin Regency. The purpose of this study was to determine how the performance of UPTD Pasar Betung employees in carrying out their duties and responsibilities as employees at the Betung Market, Banyuasin Regency. This research is a qualitative research, while the approach in this research is a case study which will explain the effectiveness of the Employee Performance of UPTD Pasar Betung, Banyuasin Regency. This study uses interview and documentation techniques as a means of collecting data. In this case, the interviewed informants were the Head of Market Management Service, Head of UPTD, Market Staff and UPTD Market, Visitors and Market Traders. Based on the results of the research and discussion that has been done previously, it is concluded that the Performance Effectiveness of the UPTD Pasar Betung which still experiences many problems, especially from internal employees such as lack of quality of employee performance on the work assigned, causes of employee timeliness and lack of employee responsibility in carrying out Duty.